2015
DOI: 10.1039/c5cc01240f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanostructured clean surface molybdenum carbides on graphene sheets as efficient and stable hydrogen evolution reaction catalysts

Abstract: Small size molybdenum carbides (2.5 nm for MoC and 5.0 nm for Mo2C) with clean surface on graphene were prepared for efficient and stable hydrogen evolution reaction catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
100
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 24 publications
0
100
0
1
Order By: Relevance
“…Among them, Mo‐based compounds, including Mo 2 C, MoN, MoP, and MoS 2 have been widely explored as effective HER electrocatalysts due to their Pt‐like electrochemical behaviors. Subsequently, to expose more active sites and improve the intrinsic electronic conductivity of Mo‐based compounds, various methods have been applied to form unique nanostructures with enriched porosity, and to introduce conductive supports, such as carbon nanosheets, carbon nanotubes (CNTs), and reduced graphene oxide (RGO) …”
Section: Introductionmentioning
confidence: 99%
“…Among them, Mo‐based compounds, including Mo 2 C, MoN, MoP, and MoS 2 have been widely explored as effective HER electrocatalysts due to their Pt‐like electrochemical behaviors. Subsequently, to expose more active sites and improve the intrinsic electronic conductivity of Mo‐based compounds, various methods have been applied to form unique nanostructures with enriched porosity, and to introduce conductive supports, such as carbon nanosheets, carbon nanotubes (CNTs), and reduced graphene oxide (RGO) …”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was shown that the TMC, molybdenum carbide, may be an efficient electrocatalyst because of its combination of structural and electronic properties . The hydrogen evolution reaction (HER) using this TMC as a catalyst is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…20,37,38 Graphene is one of the excellent carriers 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 because of its superior electro-conductivity, large surface area, and high chemical stability. So far, Mo 2 C-based catalysts, such as np-Mo 2 C nanowires, 37 porous Mo 2 C nanorods, 35 Mo 2-x Fe x C, 34 Mo 2 C/CNT-GR 20 and etc, have been demonstrated to exhibit high activity towards hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, considerable studies suggested that the HER performance of molybdenum carbide-based materials depended on their small grain size of molybdenum carbides, large surface area, and highly dispersed distribution of molybdenum carbides nanoparticles, which were closely associated with their synthesis method. 31,38 Generally speaking, chemical vapor deposition (CVD) and high temperature pyrolysis of precursors are most common preparation routes. [39][40][41][42] However, during these processes, some harmful gases such as CO, C 2 H 6 or CH 4 are commonly used in the synthesis, which are harmful to the environment and the residual chars may cover the catalytic active sites.…”
Section: Introductionmentioning
confidence: 99%